国际热爱大自然促进会大自然之歌歌词修辞格分析——以汪慈光先生的作品为代表Analysis of Rhetorical Devices in the Lyrics of “TheSongs of Loving Nature” by the International Nature Loving Federation: A Case Studyof theWorks of Mr. Wang Tzu Kuang - Cherina, Winnie; Herman, Herman (Asosiasi Program Studi Mandarin Indonesia, 2025)
摘要：国际热爱大自然促进会大自然之歌旨在赞美自然、宣扬热爱自然的文化，其歌词包含大量修辞手法。本研究以汪慈光先生创作的大自然之歌为对象，运用语言学理论和定性文献分析法，结合文献研究和访谈，归纳出其歌词使用了20 种修辞格，如比喻、拟人、排比等。歌词中还融入了道家、儒家及中国传统文化思想，凸显了大自然之歌的文学价值及其对自然之美的表达。 关键词：国际热爱大自然促进会；大自然之歌；修辞格Abstract： “The Songs of Loving Nature” of the International Nature Loving Federation(INLA) aims to praise nature and advocate a culture of nature appreciation, with its lyricsincorporating a wide range of rhetorical devices. This study focuses on the Nature Songlyricswritten by Mr. Wang Ciguang, employing linguistic theories and qualitative content analysismethods. By utilizing document analysis and interviews, the study identifies the use of 20rhetorical devices in the lyrics, such as metaphor, personification, and parallelism. Thelyricsalso draw from Daoist, Confucian, and traditional Chinese cultural thought, highlightingtheliterary value of the Nature Song and its expression of the beauty of nature. Keywords: The International Nature Loving Association; Songs of LovingNature; Rhetorical Device; Meanings